2016
DOI: 10.1177/0961000615616450
|View full text |Cite
|
Sign up to set email alerts
|

Data literacy for researchers and data librarians

Abstract: This paper describes data literacy and emphasizes its importance of data literacy. Data literacy is vital for researchers, who need to become data literate science workers and also for (potential) data management professionals. Its important characteristic is a close connection and similarity to information literacy. To support this argument, a review of literature was done on the importance of data, and the data-intensive paradigm of scientific research, researchers' expected and real behaviour, the nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 61 publications
(79 reference statements)
1
78
0
11
Order By: Relevance
“…Notes 1. See Shields (2004), Carlson et al (2011), Hogenboom et al (2011, Calzada and Marzal (2013), Twidale et al (2013), Martin (2014), Bhargava and D'Ignazio (2015), MacMillan (2015), Koltay (2015aKoltay ( , 2015b, Herzog (2015) and Frank et al (2016). 2.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…Notes 1. See Shields (2004), Carlson et al (2011), Hogenboom et al (2011, Calzada and Marzal (2013), Twidale et al (2013), Martin (2014), Bhargava and D'Ignazio (2015), MacMillan (2015), Koltay (2015aKoltay ( , 2015b, Herzog (2015) and Frank et al (2016). 2.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…Even though reproducibility of underlying research has been undermined by the prioritization of citation counts and journal prestige [18], it has the potential to allow not only the verification of research results, but also may lead to the emergence of new research questions [19] Let us add that -in the hopefully not so distant future -data citation could become a regular motivating factor for researchers to share and publish their data [20].…”
Section: Research Data Management (Rdm)mentioning
confidence: 99%
“…However, more recently library and information science (LIS) literature has focused on the importance of the research data lifecycle, with particular emphasis on aspects such as research data management and data literacy (Koltay, 2017;Federer et al, 2016) As part of its strategic direction, the Council of Australian University Librarians (CAUL) (2019) is implementing a 'Digital Dexterity Framework'. Based on the work done by Jisc as described above, it outlines 'the skills and capabilities that students will need to succeed in the workforce of the future' (p1).…”
Section: Librarymentioning
confidence: 99%
“…In addition, the authors have identified a number of operational capabilities relevant to research teams: governance (Holewa et al, 2015), information (data) management (Federer et al, 2016;Holewa et al, 2015;Koltay, 2017;Reeves & Pearlman, 2017), technology infrastructure (Galanek & Brooks, 2018;Holewa et al, 2015), analytical techniques (Solis, 2016;Reeves & Pearlman, 2017), and process agility (Fitzgerald et al, 2014;Solis, 2016). Information management, technology infrastructure and governance (i.e.…”
Section: A Proposed Model Of Digital Capability For Researchmentioning
confidence: 99%